2018
DOI: 10.1093/bioinformatics/bty821
|View full text |Cite
|
Sign up to set email alerts
|

On the viability of unsupervised T-cell receptor sequence clustering for epitope preference

Abstract: The T-cell receptor is responsible for recognizing potentially harmful epitopes presented on cell surfaces. The binding rules that govern this recognition between receptor and epitope is currently an unsolved problem, yet one of great interest. Several methods have been proposed recently to perform supervised classification of T-cell receptor sequences, but this requires known examples of T-cell sequences for a given epitope. Here we study the viability of various methods to perform unsupervised clustering of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
3

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 30 publications
1
75
0
Order By: Relevance
“…In essence, these models need to be able to understand the processes that govern the affinity between a TCR and epitope on a molecular level. This process is rather complex, because while sequence similarity seems to be related to the binding process, epitopes can be bound by varying TCRs (10)(11)(12) and TCRs can also display crossreactivity (13). Despite the advent of single cell TCR paired chain sequencing, currently available TCR-epitope binding data mostly consists of single-chain, often beta-chain, data, while in reality both the alpha-and beta-chains are thought to contribute to binding specificity.…”
Section: Introductionmentioning
confidence: 99%
“…In essence, these models need to be able to understand the processes that govern the affinity between a TCR and epitope on a molecular level. This process is rather complex, because while sequence similarity seems to be related to the binding process, epitopes can be bound by varying TCRs (10)(11)(12) and TCRs can also display crossreactivity (13). Despite the advent of single cell TCR paired chain sequencing, currently available TCR-epitope binding data mostly consists of single-chain, often beta-chain, data, while in reality both the alpha-and beta-chains are thought to contribute to binding specificity.…”
Section: Introductionmentioning
confidence: 99%
“…These peptide-specific TCRβ sequences can be utilized in a peptide-TCR interaction classifier to identify other TCRβ that are likely to react against the same HBsAg epitopes, as it has been shown that similar TCRβ sequences tend to target the same epitopes 16 Fig. 3b).…”
Section: Resultsmentioning
confidence: 99%
“…However, we do have some reasons to believe that the epitope-specific prediction models are MHC-agnostic. First, previous studies have shown that TCRs can be shared across individuals with different HLA-types (20) and that epitope-specific TCR patterns seem to transcend the MHC background of the epitopes (11). This might indicate that epitope-specific TCR sequences can recognize a specific epitope even when it is presented by different MHCs.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the epitope specificity of TCRs, machine learning models have been developed to analyze TCR sequences and predict the probability that they recognize and bind specific epitopes. These methods are based on the principle that similar TCR sequences often target the same epitope (11) and that machine learning techniques can be used to learn the molecular underpinnings that are shared by these epitope-specific TCR sequences (12)(13)(14). While these methods have been shown to be performant on small targeted data sets, their application on full repertoire datasets remains challenging.…”
Section: Introductionmentioning
confidence: 99%